Upaya Untuk Meningkatkan Minat Literasi Anak Usia Dini - Vidya Dwi Amalia Zati (Universitas Negeri Medan, 2018)
The problem of the low interest in literacy of the Indonesian people become the problem of the nation nowadays. The negative impact that often arises is that people become easy to absorb and receive hoax information that develops very quickly in society. This problem needs to be solved soon, so that people can be smarter in thinking and receiving information. It can be started from the early childhood, as this age is the most appropriate age to be taught the literacy. The literacy interest of early childhood can be taught through simple activities, such as asking children to read story books, reading fairy tales before going to bed, asking children to make shopping lists, inviting children to count, drawing and other daily activities that parents usually do together with children. It is never too late to start involving early childhood with literacy activities so that children's literacy interests can be formed early.